Enriching the experience of international mobility students through joint strategies and efforts: Feedback from international students and the success of SHARE COIL Course at Universiti Malaysia Sabah - Mohd. Rahimie Abd Karim; Wardatul Akmam Din; Datu Razali Datu Eranza (Universiti Sains Islam Malaysia, 2022)
COVID-19 pandemic and its afterward endemic phase has caused a huge change on the educational institutions, yet provided new opportunities for universities gaining new breed of online generation, and enabling universities to be more diversified and potentially to extend for hybrid teaching and learning. International mobility programme has always been a good input and resource for universities, and the experience by students completed their course have extensive influence to the junior at their respective institution, in becoming new batches of international mobility students. This paper will discuss on two different perspectives of international mobility students based on the conventional programme right before the pandemic, discussion on the feedback and several cases being mentioned, as well as the new SHARE COIL course that getting more popular amongst 32 partner universities listed under COIL. Results on the impact of SHARE COIL course enriching students experience are also being reported in this paper. The paper here provides an insight that would always be meaningful to the international mobility students came from different countries within the past many years. It is concluded that the success of international mobility programme could be much impacted by the facilitation process exercised by the international relations office of each respective universities, and requires joint effort for a great internal ecosystem. Added-value could be well obtained when there is mutual understanding and commitment between management to provide full support, international relations office to facilitate, and faculty to execute. Coordinators for mobility students and education exhibitions would indirectly impact the success of the programme as well.